Taking gambles at face value: Effects of emotional expressions on risky decisions - Winkielman, Piotr; Trujillo, Jennifer L.; Bornemann, Boris; Knutson, Brian; Paulus, Martin P. (Frontiers in Psychology, 2022)
Emotional facial expressions are ubiquitous and potent social stimuli that can signal favorable and unfavorable conditions. Previous research demonstrates that emotional expressions influence simple preference judgments and basic approach-avoidance behaviors. We examined whether emotional expressions can influence decisions such as choices between gambles. Based on theoretical models of affective cue processing, we predicted greater risk taking after positive than negative expressions. This hypothesis was tested in four experiments across tasks that varied in implementation of risks, payoffs, probabilities, and temporal decision requirements. Facial expressions were presented unobtrusively or for very brief durations. In all experiments, the likelihood of a risky choice was greater after exposure to positive versus neutral or negative expressions. Similar effects on risky choice occurred after presentation of different negative expressions (e.g., anger, fear, sadness, disgust), suggesting involvement of general positive and negative affect systems. These results highlight that incidental emotional cues can exert a valence-specific influence of on decisions, which could shape risk-taking behavior in social situations.